2012
DOI: 10.1556/achrom.24.2012.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating RP-HPLC method for analysis of the antibiotic doripenem in pharmaceutical formulation—comparison to UV spectrophotometry and microbiological assay

Abstract: Summary.A stability-indicating liquid chromatographic (LC) method with UV detection was developed for the determination of doripenem in the marketed formulation (Doribax ® 500 mg, powder for injection). A forced degradation study was conducted according to available guidelines and main references. Thermal, oxidizing, acidic and basic stress conditions were assayed to show the stability-indicating power of the method. Chromatographic separation was achieved using an isocratic elution method in a reversed-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Analytical methods for quantitation of doripenem are well reported, involving drug monitoring in biological matrices (Dailly, Bouquié, Deslasndes, Jolliet, & Lefloch, ; Ikeda et al, ; Sutherland & Nicolau, ) and drug estimation on bulk and pharmaceuticals (Cielecka‐Piontek & Jelinska, ; Kathirvel & Devalarao, ; Mendez et al, ; Michalska, Pajchel, & Tyski, ). In the drug formulation, doripenem has been estimated by instrumental techniques such as HPLC, UPLC, UV and derivative spectrophotometry and capillary electrophoresis (Cielecka‐Piontek & Jelinska, ; Mantovani et al, ; Paliosa, Garcia, Schapoval, Mendez, & Steppe, ; Reddy et al, ), all assays being developed through experimental protocols applied to analytical validation and investigating the stability‐indicating profile. Concerning stability, some studies have investigated the chemical decomposition of doripenem in reconstituted samples (Crandon, Sutherland, & Nicolau, ; Psathas, Kuzmission, Ikeda, & Yasuo, ; Reddy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods for quantitation of doripenem are well reported, involving drug monitoring in biological matrices (Dailly, Bouquié, Deslasndes, Jolliet, & Lefloch, ; Ikeda et al, ; Sutherland & Nicolau, ) and drug estimation on bulk and pharmaceuticals (Cielecka‐Piontek & Jelinska, ; Kathirvel & Devalarao, ; Mendez et al, ; Michalska, Pajchel, & Tyski, ). In the drug formulation, doripenem has been estimated by instrumental techniques such as HPLC, UPLC, UV and derivative spectrophotometry and capillary electrophoresis (Cielecka‐Piontek & Jelinska, ; Mantovani et al, ; Paliosa, Garcia, Schapoval, Mendez, & Steppe, ; Reddy et al, ), all assays being developed through experimental protocols applied to analytical validation and investigating the stability‐indicating profile. Concerning stability, some studies have investigated the chemical decomposition of doripenem in reconstituted samples (Crandon, Sutherland, & Nicolau, ; Psathas, Kuzmission, Ikeda, & Yasuo, ; Reddy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…gatifloxacin [11] and orbifloxacin [12] . From the literature review, it was concluded that different UVspectrophotometric and HPLC methods [13][14][15][16][17][18][19][20][21][22] are available for estimation of sertaconazole nitrate in pure and pharmaceutical dosage forms. There are no Microbiological analytical methods developed either by diffusion or turbidimetric method for the estimation of sertaconazole nitrate in pure and pharmaceutical dosage forms.…”
Section: Introductionmentioning
confidence: 99%